IMPLEMENTASI PENDEKATAN WHOLE LANGUAGE DALAM PENGEMBANGAN KEMAMPUAN BERBAHASA ANAK USIA DINI DALAM ERA REVOLUSI 4.0 - I Ketut Suparya (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
Early childhood education to develop moral potential and religious, social, emotional, independence, cognitive, language, motoric and artistic values for children's readiness connects elementary school level. Language development is one of the developments that need to be developed in early childhood. Through language that is permitted by children to translate experiences into symbols that can be used to communicate and think. Language development for kindergarten children based on reference to early childhood education standards No.58 of 2009, developed three aspects, namely accepting language, expressing language, and literacy. Whole language is a learning approach that teaches language in class or school in a whole and fun way. Learning to hear, speak, read and write is not carried out separately but is carried out together in an integrated manner in all areas of ability in kindergarten. Early childhood language development has a very close relationship with children's readiness in facing the 4.0 revolution era, because optimal child development will be able to stimulate all child development so that later when they are adults they will be ready to face the industrial revolution 4.0.